Fish, n–3 PUFA consumption, and pancreatic cancer risk in Japanese: a large, population-based, prospective cohort study - Hidaka, Akihisa; Shimazu, Taichi; Sawada, Norie; Yamaji, Taiki; Iwasaki, Motoki; Sasazuki, Shizuka; Inoue, Manami; Tsugane, Shoichiro (The American journal of clinical nutrition, 2015)
Most previous prospective studies in Western countries found no association between consumption of fish and n-3 (ω-3) polyunsaturated fatty acids (PUFAs), such as eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA), for which the main source is fish, and pancreatic cancer risk. However, prospective evidence is still lacking among populations who have a relatively higher fish consumption. We investigated the association between fish and n-3 PUFA consumption and pancreatic cancer risk in a population-based, prospective study in Japanese men and women. The Japan Public Health Center-based Prospective Study (JPHC study) has enrolled 140,420 subjects. We analyzed data on 82,024 eligible participants aged 45-74 y without a history of cancer who responded to a validated food-frequency questionnaire that included 138 items in 1995 for cohort I and in 1998 for cohort II. Participants were followed through 2010. HRs and corresponding 95% CIs for the highest compared with lowest quartile were calculated by using multivariable-adjusted Cox proportional hazards regression models. During 1,068,774 person-years of follow-up, 449 newly diagnosed pancreatic cancers were identified. After the exclusion of pancreatic cancer cases in the first 3 y of follow-up, we found an inverse association of marine n-3 PUFA (EPA+DPA+DHA) and DHA consumption with pancreatic cancer risk: compared with the lowest quartile, multivariate-adjusted HRs in the highest quartile were 0.70 (95% CI: 0.51, 0.95; P-trend = 0.07) and 0.69 (0.51, 0.94; P-trend = 0.03), respectively. Associations for total fish, n-3 PUFA, EPA, and DPA consumption were similar but were not significant. High n-3 PUFA, especially marine n-3 PUFAs, and DHA consumption was associated with a lower risk of pancreatic cancer in a population with a large variation in fish consumption, although the data apply to only a portion of the JPHC study subjects.